Otak Rasional dan Otak Intuitif dalam Pendidikan Islam - Husein, Adib Al; Ertanti, Dwi; Wahyudin, M.; Sukmawati, Malika; Setyawan, Ricky Jaka; Krisnawati, Rida (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2018)
Basically, Islamic Education is not able yet to maximize of using the brain of learning. Human beings still use their rational brains, they are not able yet to integrate rational brain and intuitive brain. So, the result of the education process is not like yet what it’s expect. In this journal, the authors conducted literature studies using books,e-books, and journal articles to study the rational brain and intuitive brain in Islamic education. From the study, it was hoped to find a discussion of rational brain and brain in Islamic Education.